Clinical practice with anti-dementia drugs: A revised (third) consensus statement from the British Association for Psychopharmacology. (February 2017) - O'Brien, John T; Holmes, Clive; Jones, Matthew; Jones, Roy; Livingston, Gill; McKeith, Ian; Mittler, Peter; Passmore, Peter; Ritchie, Craig; Robinson, Louise; Sampson, Elizabeth L; Taylor, John-Paul; et al.
The British Association for Psychopharmacology coordinated a meeting of experts to review and revise its previous 2011 guidelines for clinical practice with anti-dementia drugs. As before, levels of evidence were rated using accepted standards which were then translated into grades of recommendation A–D, with A having the strongest evidence base (from randomised controlled trials) and D the weakest (case studies or expert opinion). Current clinical diagnostic criteria for dementia have sufficient accuracy to be applied in clinical practice (B) and both structural (computed tomography and magnetic resonance imaging) and functional (positron emission tomography and single photon emission computerised tomography) brain imaging can improve diagnostic accuracy in particular situations (B). Cholinesterase inhibitors (donepezil, rivastigmine, and galantamine) are effective for cognition in mild to moderate Alzheimer's disease (A), memantine for moderate to severe Alzheimer's disease (A) and combination therapy (cholinesterase inhibitors and memantine) may be beneficial (B). Drugs should not be stopped just because dementia severity increases (A). Until further evidence is available other drugs, including statins, anti-inflammatory drugs, vitamin E, nutritional supplements and Ginkgo biloba, cannot be recommended either for the treatment or prevention of Alzheimer's disease (A). Neither cholinesterase inhibitors nor memantine are effective in those with mild cognitive impairment (A). Cholinesterase inhibitors are not effective in frontotemporal dementia and may cause agitation (A), though selective serotonin reuptake inhibitors may help behavioural (but not cognitive) features (B). Cholinesterase inhibitors should be used for the treatment of people with Lewy body dementias (both Parkinson's disease dementia and dementia with Lewy bodies), and memantine may be helpful (A). No drugs are clearly effective in vascular dementia, though cholinesterase inhibitors are beneficial in mixed dementia (B). Early evidence suggests multifactorial interventions may have potential to prevent or delay the onset of dementia (B). Though the consensus statement focuses on medication, psychological interventions can be effective in addition to pharmacotherapy, both for cognitive and non-cognitive symptoms. Many novel pharmacological approaches involving strategies to reduce amyloid and/or tau deposition in those with or at high risk of Alzheimer's disease are in progress. Though results of pivotal studies in early (prodromal/mild) Alzheimer's disease are awaited, results to date in more established (mild to moderate) Alzheimer's disease have been equivocal and no disease modifying agents are either licensed or can be currently recommended for clinical use.